2014
DOI: 10.1155/2014/495747
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive Control of the Rotor-Stator Rub Based on Phase Characteristic

Abstract: An impulsive control method is proposed to eliminate the rotor-stator rubbing based on the phase characteristic. The relation between the vibration energy and the phase difference suggests the starting point for controlling the rotor-stator rubbing by implementing impulse. When the contact between the rotor and the stator occurs, the impulse is implemented in -direction and -direction several times to avoid the rotor-stator rubbing. The practical feasibility of this approach is investigated by numerical simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Their study provided a theoretical reference for vibration control and the optimal design of rotating machinery. Xu et al [24] suggested an impulsive control method to eliminate the rotor-stator rubbing, based on the phase characteristic. It utilized the vibration energy and the phase difference to trigger the control of the rotor-stator rubbing by impulse.…”
Section: Introductionmentioning
confidence: 99%
“…Their study provided a theoretical reference for vibration control and the optimal design of rotating machinery. Xu et al [24] suggested an impulsive control method to eliminate the rotor-stator rubbing, based on the phase characteristic. It utilized the vibration energy and the phase difference to trigger the control of the rotor-stator rubbing by impulse.…”
Section: Introductionmentioning
confidence: 99%